GAMBARAN PENERAPAN PELAYANAN FARMASI KLINIK DI PUSKESMAS - Nur Rasdianah .; Faramita Hiola (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2022)
Clinical pharmacy services are part of the pharmaceutical service standards at the puskesmas, aiming to improve therapeutic outcomes and ensure the patient's quality of life. The study aimed to determine the suitability of 7 aspects of pharmaceutical services with pharmaceutical service standards in the application of clinical pharmacy at the puskesmas. This research is an observational study using a survey method. The study was conducted at 31 Puskesmas in Bone Bolango and Pohuwato districts, Gorontalo Province, in May-August 2021. The pharmaceutical staff in charge of pharmaceutical services is the population in this study. The total sampling technique was used in sample selection. This research instrument is a checklist compiled based on pharmaceutical service standards at the puskesmas—collected data utilizing observation and interviews with respondents. Did analysis descriptively. The results showed that assessment and prescription services and drug information services were suitable, while the other five elements were poor.